The elderly - Engdahl, Sylvia (Farminghton Hills, MI Greenhaven Press, 2011)
Discusses the elderly in the United States, including the negative stereotypes of the elderly, ethical medical treatments, and legal issues regarding the elderly.
How do negative stereotypes affect Americans' perception of the elderly? -- Bias against the elderly creates a negative view of aging / Thomas Day -- Ageism, like racism and sexism, should be challenged / Robert Butler, as told to Patrick Perry -- Negative stereotypes about the elderly are formed in early childhood / Jamie Hanlon -- Negative stereotypes about the elderly are widespread and damaging / Kay Lazar -- Positive perceptions of old age should be cultivated by the young / Ilan Shrira -- In China the elderly are honored and admired / Kelly Clady-Giramma -- Are elderly people unhappy with their lives? -- Overview: research about happiness in old age yields conflicting results / Jeanna Bryner -- Yes: old age is a time of decline and loss / Lillian B. Rubin -- Giving up driving is difficult / Anita Creamer -- Isolation in old age is depressing, especially for immigrants / Paul Kleyman -- Elderly same-sex couples may lose their right to make choices / Joe Mirabella -- No: elderly people often find happiness -- Growing old is not as unpleasant as younger adults expect it to be / Paul Taylor -- Some elderly people enjoy their old age / Jerry Large -- Old age can bring serenity, and in some cases, new achievements / Jeanne Conte -- Should more medical care be provided to the elderly? -- Yes: the elderly are not receiving all the care they need -- The need for long-term care is not being met / Jane Gross -- Government control will lead to rationing of medical treatment for the elderly / Wall Street Journal Online -- The Field of geriatric medicine is vanishing because of inadequate funding / Lewis A. Lipsitz -- No: the elderly now receive too much needless medical treatment -- The Elderly are being harmed by over medication / Margaret Cruikshank -- Some nursing home elderly get futile care / Associated press -- High-tech care for people over eighty is just too costly to be justified / Daniel Callahan -- Excessive treatment of people dying of old age is cruel / Craig Bowron -- What major problems are common among the elderly? -- Poverty among the elderly is widespread in America / Ellen O'Brien, Ke Bin Wu, and David Baer -- Homelessness is increasing among elderly adults / |r M William Sermons and Meghan Henry -- |t Some people must continue to work in old age, yet cannot find jobs / Clare Ansberry -- The Elderly are vulnerable to fraud and financial abuse / Investor protection trust -- The Elderly in nursing homes are vulnerable to abuse / David Couch -- Some elders must take drastic measures to obtain long-term care / Mary A. Fischer.
Includes bibliographical references (p. 183-188) and index.
Keywords: Older people -- United States -- Juvenile literature; Older people -- Juvenile literature